Dotawo: a Journal of Nubian Studies 3: Know-Hows and Techniques in Ancient Sudan (Punctum Books, 2016)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and critical and theoretical approaches present in post-colonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of old kingdoms. The third volume of Dotawo, guest-edited by Marc Maillot, is dedicated to Know-Hows and Techniques in Ancient Sudan. This collection of articles is the result of a workshop held at Lille University on September 5 and 6, 2013, which brought together several Sudanese archaeology scholars, from architecture to iron production through pottery and textile industry. Organized by Faïza Drici, Marie Evina, and Romain David, with the support of Charles de Gaulle-Lille 3 University and the laboratoire de recherche Halma-Ipel UMR 8164 (Centre national de recherche scientifique - CNRS), this workshop was presided over by Vincent Rondot (present Director of the Egyptian Antiquities Department of the Louvre Museum and former Director of Section française de la direction des antiquités du Soudan - SFDAS). The idea of an academic publication of this workshop in Dotawo was presented by Marc Maillot (SFDAS) in September 2014, during the 13th International Conference for Nubian Studies. The project was warmly welcomed by the editorial committee, and gave birth to a fruitful SFDAS/Dotawo cooperation that started a year ago.